Associations of ozone exposure with urinary metabolites of arachidonic acid. (December 2020) - He, Linchen; Lin, Yan; Wang, Xiangtian; Liu, Xing (Lucy); Wang, Yang; Qin, Jian; Wang, Xiaoli; Day, Drew; Xiang, Jianbang; Mo, Jinhan; Zhang, Yinping; Zhang, Junfeng (Jim)
Highlights: Arachidonic acid metabolism plays a role in platelet activation and oxidative stress. Ozone exposure is associated with altered arachidonic acid metabolism. Ozone is associated with increased platelet activation and systemic oxidative stress. The findings shed lights on biological mechanisms of ozone cardiovascular effects. Abstract: Background: Ozone (O3 ) exposure has been associated with biomarkers of platelet activation and oxidative stress. The metabolism of arachidonic acid (AA) plays an important role in platelet activation and oxidative stress. However, AA metabolic pathways have not been examined in relation to O3 and other air pollutants. Methods: Early morning urine and fasting blood were longitudinally collected up to four times from 89 healthy adults (22–52 years old, 25 women) in Changsha City, China. We measured three urinary AA metabolites, namely 11-dehydro-Thromboxane B2 (11-dhTXB2 ) produced from the arachidonic cyclooxygenase pathway, 20-hydroxyeicosatetraenoic acid (20-HETE) from the CYPs pathway, and 8-isoprostane from the non-enzymatic pathway. Urinary malondialdehyde (MDA) and 8-hydroxy-2′-deoxyguanosine (8-OHdG) were measured as indicators of oxidative damage to lipids and DNA, respectively. We measured soluble P-selectin (sCD62p) concentrations in plasma as an indicator of platelet activation. Indoor and outdoor air pollutants were measured and combined with participants' time-activity pattern to calculate personal exposure to O3, PM2.5, NO2, and SO2 averaged over 12-hour, 24-hour, 1-week, and 2-week periods prior to biospecimen collection, respectively. Linear mixed-effects models were used to examine the relationships of AA metabolites with air pollutant exposures, plasma sCD62p, and urinary MDA & 8-OHdG. Results: We found that a 10% increase in 12 h and 24 h O3 exposure were associated with increases in urinary11-dhTXB2 by 1.4% (95%, 0.1% to 2.6%) and 1.3% (0.05% to 2.5%), respectively. These associations remained robust after adjusting for co-pollutant exposures. No significant associations were observed between 11-dhTXB2 and other pollutants or between O3 exposures and other AA metabolites. All the three AA metabolites were significantly and positively associated with urinary MDA and 8-OHdG, whereas only urinary 11-dhTXB2 was significantly and positively associated with plasma sCD62p. Conclusions: A metabolite of AA from the cyclooxygenase pathway was positively associated with short-term O3 exposure, and with a plasma marker of platelet activation and two urinary markers of oxidative stress. The results suggest that O3 exposure may contribute to increased platelet activation and oxidative damages via altering the metabolism of AA.